Sinergi Kegiatan Desa Mandiri Benih dan Kawasan Mandiri Benih untuk Mewujudkan Swasembada Benih - Darwis, Valeriana (Analisis Kebijakan Pertanian, 2018)
Rice seed determines successful rice farming. Adopting quality seed will improve farm yield. Rice seed procurement programs implemented by Ministry of Agriculture (MoA) among others are Seed Self-Reliance Region Model coordinated by IAARD and Seed Self-Reliance Village managed by Directorate General of Food Crops. This paper aims to synthesize those two seed procurement programs into one program called as Seed Producer Center Village. Both programs have similarities, i.e. (a) both programs were carried out by MoA, (b) programs implementation involve Provincial and Regional Agriculture Offices, BPTP/UPBS, and BPSBTPH, and (c) encouraging seed growers to become seed producers. Requirements to integrate both programs are: (i) duties coordination of each involved agency; (ii) selection of seed growers to participate in the program; (iii) seed growers training carried out by BPSBTPH/UPBS, (iv) production inputs purchase prior to planting season, and (v) the government buys the seed produced in the program and distribute it to the rice production enhancement programs. AbstrakBenih menjadi penentu awal keberhasilan dalam budidaya tanaman. Penggunaan benih bermutu akan meningkatkan produktivitas. Program pengadaan benih yang sudah dilaksanakan oleh Kementerian Pertanian antara lain adalah Model Kawasan Mandiri Benih di bawah koordinasi Balitbangtan dan Desa Mandiri Benih di bawah koordinasi Direktorat Jenderal Tanaman Pangan. Tulisan ini menguraikan alasan dan cara mensinergikan dua program pengadaan benih ke dalam satu program dengan nama Desa Sentra Produsen Benih. Kedua program memiliki banyak kesamaan di antaranya adalah: (a) dilaksanakan dalam satu kementerian, (b) pada pelaksanaan di lapang melibatkan instansi yang sama yaitu Dinas Pertanian Provinsi dan Kabupaten, BPTP/UPBS, BPSBTPH, dan (c) menjadikan penangkar sebagai produsen benih. Dalam pelaksanaannya, sinergi kedua program membutuhkan: (i) koordinasi dan tugas masing-masing lembaga yang terlibat; (ii) pemilihan penangkar yang mau dibina; (iii) pembinaan penangkar langsung oleh BPSBTPH/UPBS, (iv) pengadaan sarana produksi sebelum masuk musim tanam, dan (v) pemerintah ikut membeli benih yang dihasilkan oleh penangkar dan mengembalikan benih tersebut ke petani sekitarnya dalam bentuk program pemerintah lainnya yang berhubungan dengan benih.
Keywords: seeds production of seeds; breeder; food self-sufficiency; produksi benih; penangkar; swasembada